Effect of Cluster Nursing Based on Risk Management Strategy on Urinary Tract Infection in Patients With Severe Craniocerebral Injury - Qiao, Hongbin; Yang, Jing; Wang, Cui (Frontiers in Surgery, 2022)
Objective: To observe the effect of cluster nursing based on risk management strategy in the management of urinary tract infection in patients with severe craniocerebral injury. Methods: Total of 116 patients with severe craniocerebral injury who were admitted to our hospital from March 2019 to March 2021 were included. They were divided into the control group (58 patients) and the observation group (58 patients). The control group received routine nursing care, the observation group received cluster nursing based on risk management strategy. The incidence of catheter associated urinary tract infection (CAUTI), the results of bacterial culture on the surface of the urinary catheter, the incidence of nursing risk events, the duration of placing the urinary catheter, the length of hospital stay, and hospital costs as well as the patient satisfaction score were compared between the two groups. The knowledge, attitude and practice scale for prevention of catheter infection and the nurses' competence evaluation scale were used to evaluate the sense-control ability and core competence of the interveners. Results: The total incidence of CAUTI in the observation group was (6.90%) lower than that in the control group (20.69%)(P<0.05). The bacterial culture results on the catheter surface of patients in the observation group before and after 6 and 12 hours of catheter cleaning were better than those of patients in the control group (P<0.05). The duration of indwelling urinary catheter, hospitalization time and hospitalization expenses of patients in the observation group were lower than those of patients in the control group (P<0.05). The incidence rate of nursing risk events in the observation group was (1.72%) lower than that in the control group (11.86%)(P<0.05). The overall satisfaction score of patients, and the control and core ability scores of nursing staff in the observation group were higher than those in the control group (P<0.05). Conclusion: Cluster nursing based on risk management strategy can effectively reduce the incidence of nursing risk events and the probability of urinary tract infection in patients with severe craniocerebral injury, shorten the duration of indwelling urinary catheter and hospitalization.